2021
DOI: 10.1097/md.0000000000028373
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for diarrhea-predominant irritable bowel syndrome

Abstract: Background: Irritable bowel syndrome (IBS) is commonly accompanied by intestinal dysfunction, and diarrhea-predominant irritable bowel syndrome accounts for approximately 23.4% of all cases of IBS. The purpose of this study was to evaluate the efficacy and safety of moxibustion in the treatment of diarrhea-predominant irritable bowel syndrome. Methods: According to the retrieval strategies, randomized controlled trials (RCTs) on moxibustion therapies for IBS-D will be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The titles and abstracts were screened, excluding the studies with inconsistent study subjects and interventions, resulting in 80 articles. Finally, the full text was read to exclude non-RCTs, duplicate publications, and studies with unavailable data, resulting in 21 RCTs in the final analysis (Figure 1) (Zhou, 2008;Zhou et al, 2009;Du, 2011;Zhang, 2012;Zhao, 2013;Zhang et al, 2017a;Zhang et al, 2017b;Wu, 2018;Fu et al, 2019;Jianan, 2019;Zheng et al, 2019;Tong, 2020;Wang et al, 2020;Ch et al, 2021;Shi et al, 2021;Wan, 2021;Wang, 2021;Wu et al, 2021;Li, 2022;Liao et al, 2022;Zhang et al, 2022).…”
Section: Literature Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…The titles and abstracts were screened, excluding the studies with inconsistent study subjects and interventions, resulting in 80 articles. Finally, the full text was read to exclude non-RCTs, duplicate publications, and studies with unavailable data, resulting in 21 RCTs in the final analysis (Figure 1) (Zhou, 2008;Zhou et al, 2009;Du, 2011;Zhang, 2012;Zhao, 2013;Zhang et al, 2017a;Zhang et al, 2017b;Wu, 2018;Fu et al, 2019;Jianan, 2019;Zheng et al, 2019;Tong, 2020;Wang et al, 2020;Ch et al, 2021;Shi et al, 2021;Wan, 2021;Wang, 2021;Wu et al, 2021;Li, 2022;Liao et al, 2022;Zhang et al, 2022).…”
Section: Literature Screeningmentioning
confidence: 99%
“…Nine studies reported the AWR threshold capacity (Figure 2) (Zhang, 2012;Zhang et al, 2017a;Fu et al, 2019;Jianan, 2019;Zheng et al, 2019;Tong, 2020;Wang et al, 2020;Wu et al, 2021;Li, 2022). The meta-analysis results indicated significant heterogeneity (I 2 = 74%, p = 0.0002).…”
Section: Awr Threshold Capacitymentioning
confidence: 99%
See 3 more Smart Citations